Effect of acid washing on pyrolysis of Cladophora socialis alga in microtubing reactor. (December 2015) - Ly, Hoang Vu; Kim, Seung-Soo; Kim, Jinsoo; Choi, Jae Hyung; Woo, Hee Chul
Highlights: Pyrolysis of macroalgae Cladophora socialis was conducted in micro tubular reactor. Acid washing affected the pyrolysis behavior of Cladophora socialis . Pyrolysis of raw and acid washed C. socialis produced bio-oils with different compositions. Pyrolysis reaction pathway was from C. socialis to liquid and then to gas (C1 –C4 ). Abstract: Cladophora socialis is a unique macroalga that is widely grown in the coastal regions of Vietnam. In this work, the pyrolysis characteristics of C. socialis were evaluated using thermogravimetric analysis (TGA) and pyrolysis in a tubing reactor. Macroalgae have a high content of inorganic compounds. These compounds result in high char content during pyrolysis of the macroalgae, which degrades the quality of the product bio-oil. In order to study this effect, C. socialis was demineralized by acid washing to remove the inorganic compounds. The effect of acid washing on the pyrolysis product distribution and the selectivity of composition in pyrolysis oil was carefully investigated. The kinetic parameters and the primary reaction pathways were also determined based on experimental data using nonlinear least-squares regression assuming a first-order kinetics model.